MARKETING RESEARCH AT INDUSTRIAL ENTERPRISES - HROMOVA, Olha; ABDULLAIEVA, Anastasiia; SHARKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Marketing is the most difficult to manage sphere of activity of the enterprise. Due to various contacts with the market (one way or another), there are numerous touch points and, as a result, as many control requirements. It is advisable that marketing activities are not limited to solving current problems, but will include, for example, projective analysis of information about customers. Therefore, in order to meet the set requirements, management systems must be flexible and multifaceted. Here the problem appears quite clearly: the management system that meets the requirements of the organization can be quite cumbersome and complex. Economic evaluations of the effectiveness of the marketing activity of an industrial enterprise must be carried out on the basis of general methodological approaches to the evaluation of production and a generally accepted system of indicators. In addition, the differences may lie only in the standards of comparison used, without changing the methodology itself and the system of evaluation indicators. The purpose of the article is to determine the current methods of marketing research in industrial markets. Industrial marketing research is a broad field of activity related to the systematic collection, processing and analysis of data in the field of marketing competence of industrial companies. Their goal is not only to identify problems, but also to identify market opportunities related to achieving the desired competitive position in a specific market.Industrial marketing research includes analysis of sales volumes and marketing opportunities, sales forecasting, and determination of market supply and demand curves. Data obtained during market research are used to perform basic management functions, such as planning and controlling the activities of the entire industrial enterprise. Industrial marketing research often involves the search for primary data when definitive research is needed or when supporting data is limited for decision making.
Keywords: marketing; marketing research; competitiveness; industrial production; mechanical engineering